Islamic Parental Involvement in Supporting School-Based Literacy Program of Young Learner - Naajihah Mafruudloh; Aries Fachriza; Nur Mafissamawati Sholikhah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Literacy is one of the important habits in academic life. In order to give a good habit in literacy, it is important to train the young learner as early as possible. During the pandemic covid-19, all of the literacy programs held by education institutions should be implemented at home. It means that the role of parents in order to support literacy programs was needed. This study aimed to investigate the Islamic parental involvement in supporting school-based literacy programs. The researcher used a qualitative descriptive research design. To obtain the data, the researchers used to survey and interview virtually. It involved 60 parents from different backgrounds of knowledge and social status. It also used snowball purposive sampling to select the research subject, because the researcher had considerations, such as the research subjects came from a Muslim background, their children were in elementary school level, etc. Based on the data result, most of the parents gave good feedback and support the school literacy program.